2021
DOI: 10.3390/foods10092009
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Salts on Structural, Physicochemical and Rheological Properties of Low-Methoxyl Pectin/Sodium Caseinate Complex

Abstract: The addition of salts is an effective way to improve the properties of polysaccharide/protein complexes for use in foods. However, there is no comparative study on the effects of different ions on the complex system of low methoxyl pectin (LMP)/ sodium caseinate (CAS) complex. The effects of different concentrations of three salt ions (Na+, K+, Ca2+) on the physicochemical and rheological properties of the LMP/CAS complex were determined in this study, and the structure of LMP/CAS complex was characterized. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 41 publications
0
2
1
Order By: Relevance
“…A previous study on citrus fiber revealed a higher RC value (40.4%) compared to the current study (31.6%), although both have a comparable hemicellulose content (approsimately 130 g kg −1 w/w) 71 . Furthermore, the RC values for CEL (44.1%) and pectin fractions (34.4–38.6%) obtained in the present study were higher than soybean hull (33%) and orange peel pectin (29.8%), respectively 29,72 . In particular, the botanical origin and the extraction method should be considered.…”
Section: Resultscontrasting
confidence: 78%
See 1 more Smart Citation
“…A previous study on citrus fiber revealed a higher RC value (40.4%) compared to the current study (31.6%), although both have a comparable hemicellulose content (approsimately 130 g kg −1 w/w) 71 . Furthermore, the RC values for CEL (44.1%) and pectin fractions (34.4–38.6%) obtained in the present study were higher than soybean hull (33%) and orange peel pectin (29.8%), respectively 29,72 . In particular, the botanical origin and the extraction method should be considered.…”
Section: Resultscontrasting
confidence: 78%
“…71 Furthermore, the RC values for CEL (44.1%) and pectin fractions (34.4-38.6%) obtained in the present study were higher than soybean hull (33%) and orange peel pectin (29.8%), respectively. 29,72 In particular, the botanical origin and the extraction method should be considered. Moreover, the results obtained in this study indicated that the insoluble fractions (DKSP and CEL) had a crystallinity higher than that of the soluble fractions (pectin and HEM).…”
Section: X-ray Diffractionmentioning
confidence: 99%
“…Dynamic light scattering (Malvern Zeta Nano ZS90, Malvern Instruments, Worcestershire, UK) was used to measure the particle size and ζ-potential of the protein-polysaccharide mixture [18]. The ζ-potentials of SPI and polysaccharides at different pH values are also shown.…”
Section: ζ-Potential Analysismentioning
confidence: 99%